Linguistic Landscapes and Cultural Identity Formation in Multilingual Urban Spaces - Fajar Pratama Rizky (Pemuda Peduli Publikasi Insan Ilmiah, 2026)
Purpose: This study aims to examine how linguistic landscapes in multilingual urban spaces reflect sociolinguistic hierarchies and contribute to processes of cultural identity formation. It seeks to understand the relationship between language visibility in public signage, power relations, and the ways urban residents negotiate belonging and recognition within the city. Subjects and Methods: The research employed a qualitative case study design grounded in linguistic landscape studies. Data were collected through systematic field observations, photographic documentation of public signage, and semi-structured interviews with community members, residents, and business owners in selected multilingual urban areas. The data were analyzed using qualitative thematic analysis, linguistic landscape categorization (top-down and bottom-up signage), and critical discourse analysis to interpret language choice, visibility, and ideological implications. Results: The findings reveal a patterned distribution of languages in urban public spaces, with the national language dominating official signage and heritage languages appearing primarily in localized, community-based contexts. Bottom-up signage demonstrated greater linguistic creativity through multilingual and mixed-language practices, functioning as sites of identity negotiation and cultural expression. Linguistic visibility was strongly associated with feelings of cultural recognition and belonging, while linguistic absence contributed to perceptions of marginalization. Conclusions: The study concludes that linguistic landscapes actively shape cultural identity and social inclusion in multilingual cities. More inclusive language policies are needed to recognize heritage languages and support equitable linguistic representation in urban public spaces.